LEXICAL MEANS OF EXPRESSING SPATIAL RELATIONS IN THE UZBEK LANGUAGE - Karimova Dilbar Eshkabilovna (Bright Mind Publishing, 2025)
This article examines the lexical means of expressing spatial relations in the Uzbek and Russian languages from the perspective of their structural-grammatical, semantic, and functional features. The analysis is based on a comparative study of the main categories of spatial vocabulary, including prepositions and postpositions, adverbs of place, as well as derivational and formal-grammatical elements involved in expressing locative and directive meanings. Special attention is paid to typological differences in the ways spatial relations are expressed, which are determined by the analytical and agglutinative nature of the Uzbek language and the inflectional system of the Russian language.
Keywords: Adlocation, delocation, translocation, semantics, absolutive, lexeme, relative, postpositions, affixes.